Ion‐Accumulation‐Induced Charge Tunneling for High Gain Factor in P–I–N‐Structured Perovskite CH3NH3PbI3 X‐Ray Detector. Issue 6 (3rd December 2021) - Jia, Shanshan; Xiao, Yingrui; Hu, Mingxin; He, Xilai; Bu, Nuo; Li, Nan; Liu, Yucheng; Zhang, Yunxia; Cui, Jian; Ren, Xiaodong; Zhao, Kui; Liu, Ming; et al.
Abstract: Lead halide perovskite‐based X‐ray detectors show very promising sensitivity and low detection limit, which can be used for next‐generation, room‐temperature radiation detections. It is interesting to find that the diode‐structured X‐ray detector shows very high photocurrent gain under small reversed bias voltage, which is unusual and should be investigated and understood for better device design. In this regard, a lead halide perovskite‐based X‐ray detector with the p–i–n structure is fabricated and studied. The p–i–n structured device shows abnormal and excellent photoconductor properties with high photocurrent gain factor under reverse bias. Further device simulation reveals that the ion migration and accumulation in the perovskite material are responsible for the large band‐bending at the interface, which may induce charge tunneling to reduce the contact resistance and causes the reverse‐biased device to work as a photoconductor rather than a photodiode. This finding provides a new approach to the understanding and design of high‐performance X‐ray detectors utilizing ionic semiconductors like lead halide perovskites. Abstract : Ion migration and accumulation at the interface will increase the band bending, which may induce charge tunneling between perovskite and hole trasnport layer/electron transport layer, making the diode device work like a photoconductive detector with high current gain.